PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 9 PARIAMAN - DEBY AULIA SIDIQA (Jurnal Edukasi dan Penelitian Matematika, 2020)
The ability of understanding mathematical concepts is one of the basic capabilities that should be owned by every learner in the learning of mathematics. There is the fact that the understanding of the concept of students of class VIII SMP Negeri 9 Pariaman is still low. It is because the learning process is centered on teachers. To overcome this, teachers need to apply the learning model that facilitates students in understanding a concept being taught with their own knowledge. Learning Model that can be used is Cooperative Learning type Two Stay Two Stray (TSTS). This research type is research of quasi-experimental design with Static Group Design. Based on the analysis of data using t-test obtained P-value=0,015 < α=0.05, so it can be concluded that the ability of understanding the concept of students who studied using Cooperative learning model Learning type TSTS better than the students who learn using conventional learning. Keywords–Cooperative Learning, Two Stay Two Stray, Mathematical Concepts, Conventional Learning.